Social work theory & practice : mastering social work practice - Deacon, Lesley; Macdonald, Stephen James
Understanding how theory informs social work practice is an area that students can often find challenging and this book aims to help students understand how theory impacts and informs social work practice across a range of contexts and with different service user groups. It starts off by briefly setting the context, introducing students to the importance of social work theory and it's development over the years, before moving on to look at different types of theory across 17 tightly structured chapters. These chapters cover a range of psychological theories, sociological theories, ethics and moral philosophies, political theories and ideologies, and organisational theories.
Introduction -- Introduction to Social Work Theory -- PART ONE -- Psychological Theories -- Psychoanalysis, psychodynamics and social work practice: the conflicted 'self' -- Behaviourism and the science of control -- Cognitive psychology and social work: a brave new world -- Humanistic psychology: a stairway to Athena -- Human growth and development -- PART TWO -- Sociological Theories -- Social constructivism and social work -- General systems and ecological theories -- Feminism and social work -- Reflexivity -- PART THREE -- Ethics and Moral Philosophies -- Deontology -- Utilitarianism -- Virtue Ethics -- Ethics of Care -- Radical Ethics -- PART FOUR -- Political Theories and Ideologies -- Radical Social Work -- Five Models of Disability -- Anti-Discriminatory Practice -- PART FIVE -- Organisational Theories -- Classical and modern management theories -- Organisational culture -- Conclusion.
Keywords: Social service; Sociology; Social psychology